Familial Factors Associated with Age at Menarche: Evidence from Mothers, Sisters, and Female Students in Elementary School in Surabaya - Putri, Ananda Wilda Sofiana Permata; Amalia, Rize Budi; Dwiningsih, Sri Ratna (Universitas Andalas, 2025)
Age at menarche is an important marker of reproductive health and varies widely among individuals. Familial factors, especially maternal and sibling age at menarche, have been identified as strong predictors that influence the onset of puberty in girls. This study aimed to analyze the association between familial factors and the age at menarche among students, their mothers, and older sisters. A cross-sectional study was conducted on 52 female students from an elementary school in Surabaya who had already experienced menarche. Data were collected using structured questionnaires and analyzed using the Chi-square test. The results showed a significant association between the students’ age at menarche and the age at menarche of their mothers and/or older sisters (p = 0.008). Students whose mothers and/or older sisters experienced menarche at an earlier age tended to reach menarche earlier as well. This pattern suggests a hereditary influence within families, indicating that maternal and sibling menarcheal history contributes substantially to determining menarcheal timing among female elementary students. These findings reinforce the role of familial factors in the biological regulation of pubertal onset.